Strategi Meraih High Quality CPR Dengan Audio Guide Pada Pembelajaran BHD - Riyana, Asep; Rahman, Arip; Hidayat, Asep AS (Universitas Galuh, 2024)
Indonesia is the country with the highest risk of disaster events in the world. Every year the figure continues to increase, including in the city of Tasikmalaya, which since the beginning of January 2022 has been declared an emergency disaster alert due to extreme weather. It is time for the community to mitigate by equipping themselves with emergency knowledge, one of which is mastery of cardio pulmonary resuscitation, which is an effort to restore a person's heart and respiratory function. The best cardio pulmonary resuscitation is high quality cardio pulmonary resuscitation which consists of 4 key actions whose implementation must be focused at a constant time. Without constant time in basic life support learning, students generally have difficulty achieving high CPR scores on the phantom lateral CPR manikin. after being given a constant tempo manually there was an increase in the CPR score. Researchers are interested in making an audio guide consisting of CPR SOP audio with constant time. This research aims to determine the potential of audio guides in producing high quality CPR. The method used was quasi experimental posttest control group design with 33 samples per group. The research results showed that learning CPR with an audio guide gave respondents a significant score as indicated by p=0.024. audio guide is effective in providing better scores in learning bhd.